Elimination Kinetics of Ethanol in a 5-Week-Old Infant and a Literature Review of Infant Ethanol Pharmacokinetics. (4th December 2013) - Ford, Jonathan B.; Wayment, Mac T.; Albertson, Timothy E.; Owen, Kelly P.; Radke, Joshua B.; Sutter, Mark E.
Abstract : Primary ethanol metabolism occurs through alcohol dehydrogenase, but minor metabolic pathways such as the P450 enzymes CYP2E1 and CYP1A2 and the enzyme catalase exist. These enzymes have distinct developmental stages. Elimination kinetics of ethanol in the infant is limited. We report the elimination kinetics of ethanol in a 5-week-old African-American male who had a serum ethanol level of 270 mg/dL on admission. A previously healthy 5-week-old African-American male was brought to the ED with a decreased level of consciousness. His initial blood ethanol level was 270 mg/dL. Serial blood ethanol levels were obtained. The elimination rate of ethanol was calculated to be in a range from 17.1 to 21.2 mg/dL/hr and appeared to follow zero-order elimination kinetics with a R 2 = 0.9787 . Elimination kinetics for ethanol in the young infant has been reported in only four previously published reports. After reviewing these reports, there appears to be variability in the elimination rates of ethanol in infants. Very young infants may not eliminate ethanol as quickly as previously described. Given that there are different stages of enzyme development in children, caution should be used when generalizing the elimination kinetics in young infants and children.